(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
A recurring problem for pre-service teacher preparation courses is the delicate challenge of selecting outstanding applicants while protecting against the admission of those who lack the necessary ability and devotion to the noble vocation of teaching. The primary goal of the teacher education programme is to assess individuals who exhibit fundamental personal qualities such as sincerity, honesty, dedication, equity, and objectivity, as well as the necessary subject matter expertise and pedagogical understanding to achieve positive results. A problem occurs when persons who lack the necessary competences and attributes for this monumental profession are admitted to the curriculum. As a result, within the area of the education system, this eventually results in the generation of educators of lesser calibre. As a result, it is essential to develop a systematic process for careful identification of persons with the innate ability to flourish in the field of pedagogy.According to the content analysis of the open-ended interviews, the most often expressed proposals by participants centred on the competitiveness of the curriculum, work placement chances, and the necessity for the development of in-demand skills. Faculty are suggested for a variety of reasons, including policy revisions, training, competitive environment and development, and enhanced human resource policies.